A Novel Method to Deliver Natural Fibre for Mechanical Reinforcement of Polyurethane Foam. Issue 3 (May 2014) - Hussain, Sadakat; Kortschot, Mark
Introducing glass fibre to polyurethane foams increases the foam stiffness without raising the isocyanate content. This allows glass fibre reinforced polyurethane foams to be used in structural applications. Glass fibre reinforced polyurethane foams can be manufactured on a large scale using a chopper gun spray system. The glass fibre is commonly supplied as a roving (long strands of fibre wound into a spool) and the chopper gun breaks the roving into equal length pieces, which delivers a stream of glass fibre at a constant mass flow rate. Residual natural fibre is cost-effective, abundant and renewable making it an ideal candidate to replace non-renewable glass fibre in reinforcing polyurethane foam. However, residual natural fibre are often supplied as loose tufts and require multiple steps to be made into roving. In this study, a novel concept was developed that can meter natural fibre at a constant mass flow rate. The concept has the potential for developing natural fibre reinforced polyurethane foams on a large scale, with uniform fibre dispersion and high fibre volume fractions. The concept is verified through mathematical simulations and a prototype.